CHI '12 Extended Abstracts on Human Factors in Computing Systems 2012
DOI: 10.1145/2212776.2223821
|View full text |Cite
|
Sign up to set email alerts
|

Kin'touch

Abstract: Tactile or interactive maps are largely used as an orientation aid for visually impaired people. Yet, little is known about haptic exploration strategies and their influence on the resultant cognitive mapping. We have designed a prototype with the potential to automatically analyze different users' exploration strategies. This prototype integrates data from the MS Kinect camera and a multi-touch table. It registers location of hands and digits on a tactile map. Results of preliminary studies show that this app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…For instance, Guerreiro et al [18] observed various two-handed strategies including symmetrical hand movements when exploring the graphic. Interestingly, new technologies make it easier to track finger movements and can improve the research in the domain by providing new methods [6] [29].…”
mentioning
confidence: 99%
“…For instance, Guerreiro et al [18] observed various two-handed strategies including symmetrical hand movements when exploring the graphic. Interestingly, new technologies make it easier to track finger movements and can improve the research in the domain by providing new methods [6] [29].…”
mentioning
confidence: 99%
“…There is also an important, steady beat of research on tactile map usability and cognition that does not necessarily involve digital or interactive maps, investigating topics including -but not limited to -symbolization (Lee, 2019;Rahardjo et al, 2019), estimating spatial relationships (Hagedorn, 2012;Simonnet et al, 2019), tactual perception (Bardot et al, 2014;Brock et al, 2012;Jansson and Monaci, 2003;Morash et al, 2014), representations of scale (Rastogi et al, 2013;Yayla, 2009), and the comparison of tactile maps to verbal descriptions (Habel et al, 2010;Koustriava et al, 2016). This research is certainly crucial for deepening our understanding of how tactile maps work and are used.…”
Section: Use and Evaluation: Access And Operationmentioning
confidence: 99%
“…They can rely on the kinesthetic perception of hand and finger movements in order to perceive the general layout of the graphic. Since several years, some researches [6,13] have proposed to explore these graphics using audio-tactile methods. For instance, Bardot et al [5] investigated the use of sparse vibratory and audio feedback to provide users with geospatial information, such as the demographics for a given region.…”
Section: Tactile Exploration Of Graphicsmentioning
confidence: 99%